Search for Higgs boson pair production with the ATLAS detector at the Large Hadron Collider - Taylor, Alan James (The University of Edinburgh, 2019)
Since the observation of a new particle consistent with the Standard Model Higgs boson by the ATLAS and CMS collaborations, a number of important measurements have been made to understand this new particle. For example, the mass has been measured to a precision of approximately 0.2% and it has been confirmed to have spin-0 and positive parity as predicted in the SM. Recently, the Higgs boson has also been observed to couple to top and bottom quarks. The Higgs mechanism also predicts that the Higgs field can interact with itself: a single virtual Higgs boson can produce two Higgs bosons. The central topic of this thesis is understanding this self-coupling property of the Higgs boson. Unfortunately the rate predicted for Higgs boson pair production is very low and the backgrounds are particularly challenging. This makes it one of the most difficult properties of the Higgs boson to measure at the Large Hadron Collider (LHC). In this thesis three contributions are presented: performance studies for the upgraded ATLAS inner detector, the prospects for observing Higgs boson pair production in association with top quarks at the High Luminosity LHC (HLLHC) and the search for Higgs boson pair production in the final state of two bottom quarks and two photons with the Run 2 data set. In the near future, the LHC will be upgraded so it can deliver higher instantaneous luminosities. In order to maintain the current detector performance in these conditions, the ATLAS detector must also be upgraded. The silicon cluster sizes, channel occupancies and cluster densities are studied in two proposed layout designs for the future ATLAS inner detector, the ITk. The differences between the two layouts are compared and these studies were used as one of many inputs into the layout design decision which was taken at the end of 2017. A number of phenomenological studies have shown that Higgs boson pair (HH) production in association with top quarks is a promising channel to study the Higgs boson self-coupling. This channel is examined with a parameterised detector response and realistic backgrounds for the first time in this thesis. It is found that the sensitivity to this process is much smaller than that predicted in the phenomenological studies. The origin of this is due to a significant underestimation of the backgrounds in the phenomenological studies. It is possible that new physics could enhance the rate of HH production, for example modifications to the Higgs boson self-coupling can increase the rate of HH production. A search is performed for HH production in the b-b γγ final state with the Run 2 data set collected by the ATLAS detector. A novel 2D fit is implemented and is found to improve the sensitivity to SM HH production by approximately 10% compared to the 1D fit which is typically used in H → γγ physics analyses. No significant deviations from the SM are observed in this analysis and 95% CL upper limits are established. The observed (expected) limit for the SM HH cross section is 10.1 (7.0) times the SM value while the ratio of the Higgs boson self-coupling to its SM prediction, κλ is observed (expected) to be constrained at 95% CL to -4:4 < κλ < 9:5 (-3:3 < κλ < 8:9).
Keywords: Large Hadron Collider; Standard Model; Higgs boson; Higgs self-coupling; SM predictions; Higgs boson pair production